Formation of a Huesler-like L21 phase in a CoCrCuFeNiAlTi high-entropy alloy. (15th April 2015) - Choudhuri, D.; Alam, T.; Borkar, T.; Gwalani, B.; Mantri, A.S.; Srinivasan, S.G.; Gibson, M.A.; Banerjee, R.
Abstract : Ordered L21 Huesler phases not only exhibit interesting magnetic properties but are also known to substantially enhance creep resistance in multi-phase alloys. We present experimental evidence of a Huesler-like ordered L21 phase in a multicomponent High Entropy Alloy (HEA) and rationalize the titanium induced stabilization of this phase based on first-principles calculations. More broadly, this paper directly shows that the composition of HEAs can be tuned to obtain the desired microstructure, and potentially tailor their properties.